Apple cider vinegar modulates serum lipid profile, erythrocyte, kidney, and liver membrane oxidative stress in ovariectomized mice fed high cholesterol - Naziroğlu, Mustafa; Güler, Mustafa; Özgül, Cemil; Saydam, Gündüzalp; Küçükayaz, Mustafa; Sözbir, Ercan (Springer, 2014)
The purpose of this study was to investigate the potentially beneficial effects of apple cider vinegar (ACV) supplementation on serum triglycerides, total cholesterol, liver and kidney membrane lipid peroxidation, and antioxidant levels in ovariectomized (OVX) mice fed high cholesterol. Four groups of ten female mice were treated as follows: Group I received no treatment and was used as control. Group II was OVX mice. Group III received ACV intragastrically (0.6 % of feed), and group IV was OVX and was treated with ACV as described for group III. The treatment was continued for 28 days, during which the mice were fed a high-cholesterol diet. The lipid peroxidation levels in erythrocyte, liver and kidney, triglycerides, total, and VLDL cholesterol levels in serum were higher in the OVX group than in groups III and IV. The levels of vitamin E in liver, the kidney and erythrocyte glutathione peroxidase (GSH-Px), and erythrocyte-reduced glutathione (GSH) were decreased in group II. The GSH-Px, vitamin C, E, and beta-carotene, and the erythrocyte GSH and GSH-Px values were higher in kidney of groups III and IV, but in liver the vitamin E and beta-carotene concentrations were decreased. In conclusion, ACV induced a protective effect against erythrocyte, kidney, and liver oxidative injury, and lowered the serum lipid levels in mice fed high cholesterol, suggesting that it possesses oxidative stress scavenging effects, inhibits lipid peroxidation, and increases the levels of antioxidant enzymes and vitamin.
WOS: 000339895800002
PubMed ID: 24894721
Keywords: Oxidative Stress; Glutathione Peroxidase; Ovariectomize; Hypercholesterolemia; Antioxidant Vitamins; Liver